Effects of active mineral additions on the concrete behavior based on demolition sands - Benaichi, Elhadj; Mezghiche, Bouzidi (Journal of Applied Engineering Science & Technology, 2018)
The exhaustion of natural aggregate deposits and the difficulties of opening new quarries make it necessary to look for new sources of supply. Recycling and recovery of waste are now considered a solution for the future in order to meet the shortfall between production and consumption and protect the environment. The objective of this study is to evaluate the effect of active mineral additions (Pozzolana, slag and silica fume) and inert (calcareous) on the behavior of concrete using recycled fine aggregates.   The results obtained in this experimental study allow us to draw the conclusion that the use of additions (pozzolana , limestone fillers, silica fume and slag) improves the physico-mechanical and, more particularly, rheological characteristics of concretes based on 50% of recycled fine aggregate.